The Bacteriocin Potential of Lactic Acid Bacteria from Cincalok as an Antibacterial Against Shigella and Salmonella - Aprilia, Ineke; Pribadhi, Adhitya Naufal; Suwanto, Yustiana Arie; Widyaningrum, Ratna; Yana, Dian Rudy; Rofiah, Nurul Ummi (Universitas Karya Husada Semarang, 2026)
Background: Lactic Acid Bacteria are a group of bacteria that have the ability to produce antimicrobial compounds called bacteriocins. Antibacterial of lactic acid bacteria proved effective in inhibiting pathogenic bacteria that cause infection in humans such as Shigella sp and Salmonella sp. Lactic acid bacteria can be found in fermented foods, one of which is fermented food typical of West Kalimantan, namely cincalok Aim: This study was to determine the antibacterial potential of cincalok lactic acid bacteria against Shigella sp and Salmonella sp Methods: This study used a true experimental, with the research design using a post test only control group design with data analyzed using SPSS to evaluate inhibition zone differences among three treatment groups: bacteriocin from Weissella sp. at 24 hours, Weissella sp. at 48 hours, and antibiotics (positive control) Results: The results obtained in the bacteriocin test from Weissella showed that there were differences in the inhibition zones formed, in Shigella sp the average values of the inhibition zones formed were W24 (24.4 mm), W48 (13.2 mm) and Cotrimoxazole (42.2 mm). while in Salmonella sp the average value of the inhibition zone formed is W24 (24.2 mm), W48 (12.8 mm) and Chloramphenicol (45 mm). Conclusion: Bacteriocins from LAB cincalok have an antibacterial effect on the growth of Shigella sp and Salmonella sp bacteria.